1997
DOI: 10.1159/000139531
|View full text |Cite
|
Sign up to set email alerts
|

The NMDA Receptor Competitive Antagonist CPP Modulates Benzodiazepine Tolerance and Discontinuation

Abstract: Benzodiazepine discontinuation is characterized by a syndrome of increased activity and reduced seizure threshold that is similar to effects mediated by the glutamatergic system. To elucidate the involvement of the glutamatergic system in benzodiazepine tolerance and discontinuation, we administered lorazepam, the NMDA antagonist CPP, and the combination of these compounds either concomitantly or consecutively to mice via osmotic pumps and evaluated pentylenetetrazole-induced seizure threshold, open-field acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Tolerance. To establish the time course of the disappearance of anticonvulsant tolerance in diazepam-withdrawn rats (6,12,24,36, and 72 h), we determined the anticonvulsant action of a challenging standard dose (17.6 mol͞kg per os) of diazepam by measuring the threshold dose of bicuculline necessary to elicit tonic-clonic convulsions. In vehicle-withdrawn rats this standard dose of diazepam increased the convulsive threshold dose of bicuculline by approximately 3-fold (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tolerance. To establish the time course of the disappearance of anticonvulsant tolerance in diazepam-withdrawn rats (6,12,24,36, and 72 h), we determined the anticonvulsant action of a challenging standard dose (17.6 mol͞kg per os) of diazepam by measuring the threshold dose of bicuculline necessary to elicit tonic-clonic convulsions. In vehicle-withdrawn rats this standard dose of diazepam increased the convulsive threshold dose of bicuculline by approximately 3-fold (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Dependence does not likely involve down-regulation of GABA A receptors because the modification of GABA A receptor subunit assembly or coupling and the down-regulation of GABAergic function associated with tolerance disappear before the onset of the withdrawal syndrome (14,21,22). In 1993, Turski and colleagues (11), and successively others (23,24), suggested that an enhanced glutamatergic transmission is a possible component of BZ-RS ligands withdrawal syndrome characterized by tremors, myoclonic jerks, wet dog shakes, piloerection, loss of body weight, excitability, anxiety, and electroencephalographic seizure pattern. Pharmacological experiments with agonists or antagonists of specific glutamate receptor subtypes suggested that whereas N-methyl-D-aspartate (NMDA)-dependent mechanisms may underlie the expression of signs of dependence, AMPA receptor activation may be essential for the induction of the withdrawal syndrome following a protracted diazepam administration.…”
mentioning
confidence: 99%
“…Also, lorazepam-induced tolerance to its acute anticonvulsant effects was partially prevented with simultaneous CPP treatment [122]. In contrast, the development of tolerance to the anxiolytic effects of diazepam in a social interaction test was not blocked by concomitant administration of dizocilpine [123].…”
Section: Mechanisms Underlying Tolerancementioning
confidence: 99%
“…Several studies have also provided evidence for a role for NMDA receptor antagonists in blocking the behavioral components of BZ tolerance and withdrawal File and Fernandes, 1994;Koff et al, 1997;Tsuda et al, 1998a, b). However, the contribution of AMPA receptors is less well explored.…”
Section: Introductionmentioning
confidence: 99%